The Influences of Seed Source on Germination and Production of Abnormal Seedling in Big-Leaf Mahogany (Swietenia macrophylla King) - Durai, M. V. (Indian Forester, 2020)
The big-leaf mahogany is one of the fast growing and highly demanded tropical timber species in the world. It is widely grown as an avenue tree as well as commercial plantations due to narrow crown, straightness, wide adaptability and desirable wood qualities. The morphological evaluation and grading of seedling at the early is one of most important aspects for quality planting stock production. The present study was attempted to document the influence of seed source on germination and occurrence of abnormal seedlings in big-leaf mahogany. A total of 25 seed sources collected from Tamil Nadu, Kerala and Karnataka was used in this study. The 100-seed weight, germination % and number of abnormal seedlings were recorded. The results revealed that the seed source had significant influence on these parameters. The highest germination and branched seedlings were found in Karnataka seed sources. The abnormal seedlings percent was high in Mayampady (Tamil Nadu) where as it was absent in Chaliyarmukku (Kerala).